Increased Efficiency of Current‐Induced Motion of Chiral Domain Walls by Interface Engineering. Issue 10 (4th February 2021) - Guan, Yicheng; Zhou, Xilin; Ma, Tianping; Bläsing, Robin; Deniz, Hakan; Yang, See‐Hun; Parkin, Stuart S. P.
Abstract: Magnetic racetrack devices are promising candidates for next‐generation memories. These spintronic shift‐register devices are formed from perpendicularly magnetized ferromagnet/heavy metal thin‐film systems. Data are encoded in domain wall magnetic bits that have a chiral Néel structure that is stabilized by an interfacial Dzyaloshinskii–Moriya interaction. The bits are manipulated by spin currents generated from electrical currents that are passed through the heavy metal layers. Increased efficiency of the current‐induced domain wall motion is a prerequisite for commercially viable racetrack devices. Here, significantly increased efficiency with substantially lower threshold current densities and enhanced domain wall velocities is demonstrated by the introduction of atomically thin 4d and 5d metal "dusting" layers at the interface between the lower magnetic layer of the racetrack (here cobalt) and platinum. The greatest efficiency is found for dusting layers of palladium and rhodium, just one monolayer thick, for which the domain wall's velocity is increased by up to a factor of 3.5. Remarkably, when the heavy metal layer is formed from the dusting layer material alone, the efficiency is rather reduced by an order of magnitude. The results point to the critical role of interface engineering for the development of efficient racetrack memory devices. Abstract : The efficiency of current‐induced domain wall motion in both ferromagnetic/heavy metal and synthetic antiferromagnet systems is significantly enhanced via the insertion of atomically thin dusting layers at the ferromagnet/heavy metal interface. The enhancement is due to the tuning of the strength of the Dzyaloshiskii–Moriya interaction and the effective magnetic uniaxial anisotropy energy.